Botulinum toxin injections in jaw-opening dystonia. The lateral pterygoid – maxillary artery problem. (July 2022) - Ünal, Sena; Tugra Karaarslan-Turk, F.; Cenk Akbostancı, M.; Peker, Elif; Yilmaz, Rezzak
Highlights: Lateral pterygoid muscle (LPM) is the main target for BoNT in jaw-opening dystonia. Variations in the maxillary artery close to the LPM is important in BoNT injections. The maxillary artery (MA) passes lateral to the LPM in 2/3 of the Caucasians. An extraoral approach in injections may cause MA injury, pain and hematoma. Intraoral approach should be preferred in patients with jaw-opening dystonia. Abstract: It has been suggested that the variations in the trajectory of the maxillary artery (MA) near the lateral pterygoid muscle (LPM) play a critical role in Botulinum neurotoxin (BoNT) injections in patients with jaw-opening/deviation dystonia (JOD). In the case of a lateral course to the LPM, an extraoral injection entails risks of MA injury, pain, and hematoma. Previous reports suggest geographical differences in variations of the MA-LPM relationship. We aimed to determine these variations in Turkish individuals and highlight the need to establish a consensus on approach to LPM injections. In 284 individuals, contrast-enhanced magnetic resonance angiography (MRA) images were evaluated by two radiologists on both sides for the variations in the course of the MA in the infratemporal fossa. Images of 44 were excluded due to trauma, arteriovenous malformation, mass, surgery, and imaging artifacts. Of the included, 62.1% were female. In 480 evaluations of 240 individuals, the MA passed lateral to the LPM in 65.6% (n = 315). No sex difference was noted. In 51 individuals (21.3%), the MA course differed on the right and left sides (medial–lateral asymmetry). These results confirm that the lateral course of the MA is more frequent. In patients with JOD, the trajectory of the MA should be determined with imaging prior to extraoral BoNT injections. In the case of a lateral course, an intraoral approach seems to be safer to avoid a potential MA injury.